Effect of organic nitrogen sources on yield, nutrient uptake and soil health under rice (Oryza sativa) based cropping sequence - YADAV, S K; SINGH, YOGESHWAR; YADAV, M K; BABU, SUBHASH; SINGH, KALYAN (The Indian Journal of Agricultural Sciences, 2013)
A two year of field experimentation was carried out at Varanasi from 2005–07 to study the effect of organic nitrogensources on yield, nutrient uptake and soil health under rice (Oryza sativa) based cropping sequence. The soil was sandyclay loam in the texture with pH 7.4, moderately fertile, being low in organic carbon (0.50%), available nitrogen (185.5kg/ha). The experiment on rice based cropping sequences with 3 organic N nutrition treatments was laid out in split plotdesign with three replications. Seven rice based cropping sequences [rice-potato-onion; rice-green pea-onion; rice-potatocowpea (green pod); rice-green pea – cowpea (green pod); rice-rajmash (green pod)- onion; rice-rajmash (green pod)cowpea (green pod) and rice-maize (green cob)-cowpea (vegetable)] were assigned to main plots and three treatments comprising nitrogen application (control; organic manure; organic manure + bio-fertilizer) were allocated to sub plots. The system productivity was the highest (355.73 q/ha) with rice–potato–onion cropping sequence under investigation. Among the manurial treatment, organic nitrogen nutrition with biofertilizers had the highest rice grain equivalent yield (353.08 q/ha) and net monetary return (Rupees,292 454). The application of organic manure alone or along with biofertilizers inoculation significantly improved the N, P, K and S uptake by cropping sequence over control. However maximum improvement in soil health related to soil organic carbon, available nutrient status, soil micro-organism population were observed in organic nitrogen sources alone or along with biofertilizers.